1999
DOI: 10.1038/sj.cdd.4400560
|View full text |Cite
|
Sign up to set email alerts
|

Ursodeoxycholic acid prevents cytochrome c release in apoptosis by inhibiting mitochondrial membrane depolarization and channel formation

Abstract: The hydrophilic bile salt ursodeoxycholic acid (UDCA) is a potent inhibitor of apoptosis. In this paper, we further characterize the mechanism by which UDCA inhibits apoptosis induced by deoxycholic acid, okadaic acid and transforming growth factor b1 in primary rat hepatocytes. Our data indicate that coincubation of cells with UDCA and each of the apoptosis-inducing agents was associated with an approximately 80% inhibition of nuclear fragmentation (P50.001). Moreover, UDCA prevented mitochondrial release of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
211
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(225 citation statements)
references
References 66 publications
12
211
1
1
Order By: Relevance
“…However, these modulating properties of UDCA on mitochondrial permeability transition have been conducted in isolated mitochondria, and to our knowledge a physical interaction between UDCA and membranes in the intact cell has never been shown. 13 By using a red fluorescent mitochondrial probe and a green fluorescent UDCA we show that UDCA is able to colocalize with the mitochondrial membrane after incubation with hepatocytes providing support to the theory that one component of UDCA's protective action may be related to interaction with mitochondria. The finding that TCDCA also protected against Fas-L-mediated apoptosis was at first surprising but is consistent with recent studies showing that TCDCA is capable of inducing signal transduction pathways in hepatocytes that activate NF-B anti-apoptotic pathways.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, these modulating properties of UDCA on mitochondrial permeability transition have been conducted in isolated mitochondria, and to our knowledge a physical interaction between UDCA and membranes in the intact cell has never been shown. 13 By using a red fluorescent mitochondrial probe and a green fluorescent UDCA we show that UDCA is able to colocalize with the mitochondrial membrane after incubation with hepatocytes providing support to the theory that one component of UDCA's protective action may be related to interaction with mitochondria. The finding that TCDCA also protected against Fas-L-mediated apoptosis was at first surprising but is consistent with recent studies showing that TCDCA is capable of inducing signal transduction pathways in hepatocytes that activate NF-B anti-apoptotic pathways.…”
Section: Discussionmentioning
confidence: 74%
“…8 In contrast, hydrophilic bile acids such as ursodeoxycholic (UDCA) and tauro-ursodeoxycholic acid (TUDCA) seem to be able to protect hepatocytes from apoptosis induced by a variety of different stimuli. 8,11,12 For example, UDCA prevents cytochrome c release from the mitochondria 13 probably by modulating the mitochondrial membrane permeability transition and production of reactive oxygen species. 7,8 These in vitro studies are also supported by the in vivo observation that UDCA administration prevents the increase of apoptotic hepatocytes in rats fed DCA.…”
mentioning
confidence: 99%
“…For cytochrome C measurements, cytosolic proteins were prepared by homogenization and differential centrifugation in isolation buffer as described. 25 Protein concentration was determined using BCA protein assay kit (Pierce, Rockford, IL).…”
Section: Methodsmentioning
confidence: 99%
“…23 In vitro studies showed that UDCA prevented apoptosis induced by deoxycholic acid, ethanol, transforming growth factor ␤, Fas ligand, and okadaic acid by decreasing mitochondrial depolarization with subsequent inhibition of cytochrome C release and caspase activation. 24,25 However, although some studies suggested an effect of bile acids on calcium homeostasis, [26][27][28][29] there are no data regarding the role of UDCA during ER stress-induced apoptosis.…”
mentioning
confidence: 99%
“…[18][19][20] ER stress is caused by glucose or nutrient deprivation, viral infections, lipids, increased synthesis of secretory proteins, and expression of mutant or misfolded proteins, and has been recently implicated in human diseases, such as Alzheimer's disease, Parkinson's disease, diabetes mellitus, and liver disease. [21][22][23][24] In this study, a rat steatohepatitis model induced by a methionine-choline-deficient diet (MCDD) for 10 weeks was used to obtain evidence for the resolution of fibrosis in fatty liver after changing the diet to a methionine-choline control diet (CD). The manifestation of ER stress was also studied.…”
mentioning
confidence: 99%